2013
DOI: 10.1159/000353877
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Gonadal and Gene Expression Changes throughout Development in Fathead Minnow

Abstract: Although fathead minnows (Pimephales promelas) are commonly used as a model fish in endocrine disruption studies, past studies have not characterized sex-specific baseline expression of genes involved in sex differentiation during development in this species. Using a sex-linked DNA marker to verify gender, we evaluated the expression over time of genes involved in sex differentiation (dmrt1, cyp19a, cyp17, star, esr1, ar) in developing fathead minnows (10-45 days post hatch). Evaluation of these molecular mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…), air‐breathing catfish Claris gariepinus (Raghuveer, Senthilkumaran, Sudhakumari, Sridevi, Rajakumar, Singh, Murugananthkumar & Majumdar ) and fathead minnow (Leet et al . ). Considering the age and maturity state of fish, it seems undifferentiated great sturgeon here was under 6‐month old and the observed differences would be due to the sexual developmental stages difference.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…), air‐breathing catfish Claris gariepinus (Raghuveer, Senthilkumaran, Sudhakumari, Sridevi, Rajakumar, Singh, Murugananthkumar & Majumdar ) and fathead minnow (Leet et al . ). Considering the age and maturity state of fish, it seems undifferentiated great sturgeon here was under 6‐month old and the observed differences would be due to the sexual developmental stages difference.…”
Section: Discussionmentioning
confidence: 97%
“…), shovelnose sturgeon Scaphirhynchus platorynchus (Amberg et al . ), Atlantic cod Gadus morhua (Johnsen, Seppola, Torgersen, Delghandi & Andersen ) and fathead minnow Pimephales promelas (Leet, Lesteberg, Schoenfuss, Olmstead, Amberg, Ankley & Sepúlveda ), dmrt1 mRNA expressed in both male and female gonads. Potential forms of dmrt1 have been reported in shovelnose sturgeon Scaphirhynchus platorynchus (Amberg et al .…”
Section: Discussionmentioning
confidence: 99%
“…While Zhang et al (2015) confirmed that sediment was a major source of agrichemical exposure for adult fish, this may not hold true for larvae whose interactions with sediment and water may differ from adult fish. A biological explanation for the absence of defeminization is that the expression profile of estrogen receptors in fathead minnow, namely receptor subtypes α, β and γ, has been shown to vary over the course of ontogeny which would determine what type of response larvae and juvenile fish might have towards an anti-estrogenic mixture (Filby and Tyler 2007;Johns et al 2011;Leet et al 2013). Therefore, while subtle differences were observed between the responses of larvae from the present study and those observed in adult fish from previous studies there is evidence for a consistent response of fish towards agrichemical pulses.…”
Section: Tablementioning
confidence: 99%
“…The samples most likely represent males given that arom has been shown to not be expressed by fathead minnow males through 45 dph. 28,29 Morphometric Assessment. No significant differences were detected in female body mass, GSI (Table S5, ANOVA, p values ≥ 0.25) or length (Table S5, Wilcoxon, p value = 0.14).…”
Section: ■ Resultsmentioning
confidence: 99%